2021
DOI: 10.3389/fsurg.2021.737529
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prior Intra-articular Injections on the Risk of Prosthetic Joint Infection Following Total Joint Arthroplasty: A Systematic Review and Meta-Analysis

Abstract: Objective: The current review was designed to assess the impact of prior intra-articular injections on the risk of prosthetic joint infection (PJI) in patients undergoing total joint arthroplasty (TJA) with a focus on the timing of injection before surgery.Methods: The databases of PubMed, Embase and Google Scholar were searched up to 15th June 2021. All studies comparing the incidence of PJI with and without prior intra-articular injections were included. Risk ratios (RR) with 95% confidence intervals were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Although previous systematic reviews have evaluated the association between pre‐operative IAIs and the risk of PJI, these analyses have been underpowered [10, 43], failed to segregate total hip and total knee arthroplasty patients [9, 26], or did not report on the time frames between injection and primary TKA [22]. Notably, Nie and Li [27] recently conducted a similar study among total joint arthroplasty (TJA) patients receiving pre‐operative intra‐articular injections. However, as their 3‐month sub‐analysis was comparatively underpowered, they failed to identify an increased PJI risk within this pre‐operative interval.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous systematic reviews have evaluated the association between pre‐operative IAIs and the risk of PJI, these analyses have been underpowered [10, 43], failed to segregate total hip and total knee arthroplasty patients [9, 26], or did not report on the time frames between injection and primary TKA [22]. Notably, Nie and Li [27] recently conducted a similar study among total joint arthroplasty (TJA) patients receiving pre‐operative intra‐articular injections. However, as their 3‐month sub‐analysis was comparatively underpowered, they failed to identify an increased PJI risk within this pre‐operative interval.…”
Section: Discussionmentioning
confidence: 99%
“…When THA is performed in patients who have received a steroid injection within 3 months, researchers have found an association with increased risk of periprosthetic joint infection. Such findings suggest that injected patients should delay THA for at least 3 months after the injection, prolonging the treatment process due to the unnecessary use of an injectable [45,53,60]. Thus, the decision to inject an unfit patient results from a lack of education and incomplete understanding of the risk of inappropriate injection.…”
Section: Discussionmentioning
confidence: 99%
“…42 A recent systematic review showed a statistically significant increased risk of prosthetic joint infection with administration of intra-articular injections <12 months before surgery. 43 Specifically to shoulder arthroplasty, patients who receive corticosteroid injection <3 months prior to anatomic or reverse shoulder arthroplasty were reported to have a significantly increased risk for revision. 44 Sleep apnea could have a negative impact on bone mineralization, cognition, and immunity and increases the overall rate of medical postoperative complications.…”
Section: Discussionmentioning
confidence: 99%